STARTEGI PENINGKATAN KUALITAS LAYANAN PENDIDIKAN ANAK USIA DINI DI TK DEWI SARTIKA KECAMATAN BERGAS - Amelia Dian Endarini; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The early childhood education unit is an educational unit that provides educational services for early childhood whose role is to provide stimulants that support children's growth and development. Providing quality educational services is not only the responsibility of the principal, but also teachers and parents. All these parties must have effective ways to improve the quality of PAUD services at Dewi Sartika Kindergarten. This research is qualitative research using interview, observation and documentation data collection techniques. Where this approach is taken to explore the information involved to find out the obstacles faced in efforts to improve the quality of early childhood education services. The data analysis technique used is interactive model analysis, namely data reduction, data presentation, and drawing and testing conclusions. As for testing the validity of the data by triangulating sources and techniques. The result of this research is a strategy to improve the quality of early childhood education services by the Principal of the School, preparing the curriculum contextually, increasing HR competency, programmed supervision and optimizing the role of parents. Teachers understand the stages of child development, plan learning, implement and assess learning authentically and in a culture of reflection. Meanwhile, parents appreciate the teacher's ability to guide students, the cleanliness of the learning environment and the good management of infrastructure. Key: Strategy, Service Quality, Early Childhood Education